'MONS MANUFACTUS': ROME'S MAN-MADE MOUNTAINS BETWEEN HISTORY AND NATURAL HISTORY (c. 1100–1700). (22nd May 2017) - Donkin, Lucy
Abstract : Rome's man-made mounds occupy a position between built antiquities and natural features. In the Middle Ages and early modern period, particular attention was paid to Monte Testaccio, the Mausoleum of Augustus, and the related 'mons omnis terra'. Debate focused on the origins and composition of the mounds, thought to contain either earth brought to Rome as symbolic tribute, pottery used to hold monetary tribute, or pottery produced locally. Developing over time in different genres of writing on the city, these interpretations were also employed in works on historical, religious and geological themes. The importation of material, expressive of relations between Rome and the wider world in antiquity, was used to draw positive and negative comparisons with present-day rulers and the papacy, and to associate Rome with Babylon. The growth of the mounds and the presence of ceramics were invoked in discussions of the formation of mountains and montane fossils. If the mounds' ambiguities facilitated their incorporation into other debates, the terms in which they are discussed reflect ongoing engagement with literature on the city. The reception of these monuments thus offers a distinctive perspective on the significance of Rome to connections between spheres of knowledge in this period. Abstract : A Roma le colline artificiali, frutto dell'azione umana, possono essere considerate una sorta di via di mezzo tra antichità costruite e realtà naturali. Nel Medioevo e nel periodo moderno particolare attenzione è stata data al Monte Testaccio, al Mausoleo di Augusto e al relativo ' mons omnis terra '. In particolare il dibattito si è focalizzato sulle origini e sulla composizione di questi rilievi. Si è pensato che contenessero o terra portata a Roma come un tributo simbolico, o ceramiche utilizzate per contenere tributi monetari, o ceramiche prodotte localmente. Sviluppandosi nel corso del tempo in relazione a diversi tipi di scritti sulla città, queste interpretazioni sono state utilizzate anche in lavori su tematiche storiche, religiose e geologiche. L'importazione di materiale, espressione delle relazioni ad ampio raggio di Roma nel mondo antico, è stata usata per tracciare confronti in positivo o in negativo con governanti contemporanei e il papato, e per associare Roma con Babilonia. La 'crescita' di queste colline artificiali e la presenza di ceramiche sono state chiamate in causa nelle discussioni sulla formazione di montagne e fossili montani. Se l'ambiguità di queste strutture ha facilitato il loro inserimento in altri dibattiti, i termini nei quali sono state discusse riflettono tuttavia anche il continuo interesse nei confronti di Roma. La ricezione di questi monumenti perciò offre una prospettiva peculiare del significato di Roma con connessioni tra diverse sfere di conoscenza.